Brn-2 represses microphthalmia-associated transcription factor expression and marks a distinct subpopulation of microphthalmia-associated transcription factor-negative melanoma cells. - Goodall, J; Carreira, S; Denat, L; Kobi, D; Davidson, I; Nuciforo, P; Sturm, R; Larue, L; Goding, C (2008)
The origin of tumor heterogeneity is poorly understood, yet it represents a major barrier to effective therapy. In melanoma and in melanocyte development, the microphthalmia-associated transcription factor (Mitf) controls survival, differentiation, proliferation, and migration/metastasis. The Brn-2 (N-Oct-3, POU3F2) transcription factor also regulates melanoma proliferation and is up-regulated by BRAF and beta-catenin, two key melanoma-associated signaling molecules. Here, we show that Brn-2 also regulates invasiveness and directly represses Mitf expression. Remarkably, in melanoma biopsies, Mitf and Brn-2 each mark a distinct subpopulation of melanoma cells, providing a striking illustration of melanoma tumor heterogeneity with implications for melanoma therapy.